Open Data in Global Environmental Research: The Belmont Forum's Open Data Survey. - Birgit Schmidt; Birgit Gemeinholzer; Andrew Treloar (PLoS ONE, 2016)
This paper presents the findings of the Belmont Forum's survey on Open Data which targeted the global environmental research and data infrastructure community. It highlights users' perceptions of the term "open data", expectations of infrastructure functionalities, and barriers and enablers for the sharing of data. A wide range of good practice examples was pointed out by the respondents which demonstrates a substantial uptake of data sharing through e-infrastructures and a further need for enhancement and consolidation. Among all policy responses, funder policies seem to be the most important motivator. This supports the conclusion that stronger mandates will strengthen the case for data sharing.